2016
DOI: 10.1007/s40263-016-0393-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Antagonists as Disease-Modifying Therapy for Parkinson’s Disease: Therapeutic Rationale and Current Status

Abstract: Parkinson's disease is a disabling hypokinetic neurological movement disorder with unknown aetiology in the majority of cases. Current pharmacological treatments, though effective at restoring movement, are only symptomatic and do nothing to slow the progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…Curiously, users of dihydropyridine calcium channel-blocker drugs-which target the L-type voltage-sensitive Cav1.3 channels expressed by dopaminergic neurons of the SN-are at decreased risk for PD [289][290][291][292][293]. This might reflect the fact that, whereas healthy mitochondria can buffer the episodic flux of calcium through these channels-which function as rhythmically-activated pacemakers in dopaminergic neurons of the SN-maintaining a basal dopaminergic tone-impaired mitochondria does so less effectively, leaving neurons exposed to toxic intracellular calcium levels [294].…”
Section: Controlling Intracellular Calcium With Calcium Channel-blockmentioning
confidence: 99%
“…Curiously, users of dihydropyridine calcium channel-blocker drugs-which target the L-type voltage-sensitive Cav1.3 channels expressed by dopaminergic neurons of the SN-are at decreased risk for PD [289][290][291][292][293]. This might reflect the fact that, whereas healthy mitochondria can buffer the episodic flux of calcium through these channels-which function as rhythmically-activated pacemakers in dopaminergic neurons of the SN-maintaining a basal dopaminergic tone-impaired mitochondria does so less effectively, leaving neurons exposed to toxic intracellular calcium levels [294].…”
Section: Controlling Intracellular Calcium With Calcium Channel-blockmentioning
confidence: 99%
“…Previous work has demonstrated the utility of immunotherapy to reduce aSyn levels in the CNS (Masliah et al, 2005 ) and prevent possible trans-synaptic spread of toxic aSyn species (Bae et al, 2012 ). A retrospective analysis demonstrated that the use of dihydropyridines correlates with decreased probability of developing PD (Pasternak et al, 2012 ), and an LTCC antagonist isradipine is currently in phase III clinical trials as a disease-modifying therapy for PD (Swart and Hurley, 2016 ). Combining these approaches with drugs that reduce toxic DA species might provide additional benefits.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Recently, it was showed that the treatment with L-type CCBs, such as isradipine, reduces motor symptoms and attenuates progressive death of dopamine neurons from substantia nigra in animal model of Parkinson's disease [19]. It was showed that isradipine produces a dose-dependent sparing of dopaminergic fibers, and cell bodies at concentrations achievable in humans [20], suggesting that L-type CCBs are potentially viable neuroprotective agents for Parkinson's disease. A phase II clinical trial published in 2016 showed that treatment with isradipine was safely tolerated to reduce motor symptoms by patients with Parkinson's disease [20].…”
Section: + /Camp Signalling Interaction In Neuroprotectionmentioning
confidence: 99%
“…It was showed that isradipine produces a dose-dependent sparing of dopaminergic fibers, and cell bodies at concentrations achievable in humans [20], suggesting that L-type CCBs are potentially viable neuroprotective agents for Parkinson's disease. A phase II clinical trial published in 2016 showed that treatment with isradipine was safely tolerated to reduce motor symptoms by patients with Parkinson's disease [20]. In addition, a 10-year follow-up study (2000 to 2010), involving 82,107 hypertensive patients of more than 60 years of age, showed that use of L-type CCBs reduced blood pressure, and risk of dementia in hypertensives patients, suggesting that these drugs could be clinically used to treat AD [21].…”
Section: + /Camp Signalling Interaction In Neuroprotectionmentioning
confidence: 99%